The effect of socio-economic status (SES) on health status: a systematic review of literatures - Lee, Wei Rong; Zainudin, Zaida Nor; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Socio-economic has long recognized as a significant factor affecting the health status. Lower socio-economic status has always been categories as low chance of getting the healthcare service or resources. This study is aims to determine effect of different level of socio-economic status on health status. Besides, we are looking how counselling help may differ between the groups of socio-economic status. Scopus, Science direct and Medline searched to identify research published between 2014 and 2018, which had reporting about the socio-economic status and health. A total 10-journal article selected for present a systematic review. 90% of the article reported that inequality in the socio-economic status has been affected the health of people. Lower socio-economic status people need more concern from the society and better health care service for them to increase the health status.